Immunogenetics of Trichuris muris infection - Else, Kathryn J. (1989)
Investigations have been made into the genetic control of immunity to the nematode Trichuris muris. Both background genes and genes within the mouse major histocompatibility complex (MHC), H-2, were shown to influence the expulsion of T. muris with the former having the stronger influence. At least two genes within the H-2 complex determined response phenotypes, the effects of "resistance" or "susceptibility" alleles at I-A being modulated by resistance or susceptibility alleles at aD end locus/loci. Differential responsiveness within slowly responding mouse strains suggested that parasite-dependent effects were also important. The primary antibody response to T. muris excretory/secretory (E/S) antigen, predominantly an IgG response, was also shown to be controlled by background and H-2-linked genes. In general, mouse strains less resistant to infection developed higher levels of IgG than- more resistant strains of mice. However strains of mice possessing the H-2q haplotype, irrespective of their genetic background, rapidly developed higher levels of IgG1 antibodies than strains of other haplotypes, H-2q haplotype mice tending to be more resistant to infection. Recognition of two high molecular weight (MW) E/S antigens by IgG as revealed by immunoprecipitation was also found to be almost exclusively H-2q restricted. This restriction may be partly quantitative but as such would operate in vivo due to the restriction on the ability to produce high levels of specific IgG. Both H-2q restricted phenomena may be part of, but not absolute requirements for, protective immunity. Parasite-induced effects on host immunity were also studied. Later larval and adult stages of T. muris were shown to be immunosuppressive, immunosuppression being long lasting and preventing the expulsion of subsequent infections. Vaccination with E/S antigen was shown to protect strains of mice which are slow to expel worms (poor-responder) or totally unable to expel worms (non-responder) from a primary infection with T. muris. However protection was slow to be expressed. Antigen recognition profiles of vaccinated strains of mice differed from their primary infection recognition profiles and included the recognition of the two high MW antigens shown to be H-2q restricted in a primary infection. Thus altering the mode or route of E/S antigen presentation may lead to shifts in responsiveness of H-2 genotypes to specific determinants and/or boost specific antibody levels sufficiently to reveal recognition of these antigens. Prior experience of a patent primary infection prevented vaccination protecting non-responder mice against subsequent infections. This inability was correlated with suppressed IgG1 antibody levels and failure to recognise three high MW antigens including the IL-2q restricted antigens. Using a panel of monoclonal antibodies raised against E/S antigen it was shown that E/S antigens, apparently including both immunogenic and immunosuppressive molecules, were localised to granules within the stichocyte cytoplasm of the adult T. muris stichosome.